2020
DOI: 10.1016/j.heliyon.2020.e04697
|View full text |Cite
|
Sign up to set email alerts
|

How can Azerbaijan meet its Paris Agreement commitments: assessing the effectiveness of climate change-related energy policy options using LEAP modeling

Abstract: Azerbaijan has committed to cut GHG emissions by 35% by 2030 under the Paris Agreement. By applying LEAP, a well-regarded forecasting model based on inventories defined under the IPCC (Intergovernmental Panel on Climate Change), GHG emissions projections are modeled in three scenarios: a without measures (WOM) scenario or business-as-usual, which assumes no change to current behavior, a with existing measures (WEM) scenario, which takes into account currently planned measures in Azerbaijan, and an EU policy sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Many publications used LEAP as a tool to develop and analyze energy models. The LEAP model implements integrated scenario analysis in air pollutant reduction [22]. This study showed the capability of LEAP to develop, analyze, and compare different scenarios to reduce air pollutants from the energy sector, and the viability of the model can be comprehensively analyzed using LEAP.…”
Section: A Leap Modelmentioning
confidence: 96%
“…Many publications used LEAP as a tool to develop and analyze energy models. The LEAP model implements integrated scenario analysis in air pollutant reduction [22]. This study showed the capability of LEAP to develop, analyze, and compare different scenarios to reduce air pollutants from the energy sector, and the viability of the model can be comprehensively analyzed using LEAP.…”
Section: A Leap Modelmentioning
confidence: 96%
“…Over the past decade, from 2010 to 2020, all fuel tariffs in South Africa have seen a signi cant increase, with an approximate growth of 100% [15]. This dramatic surge in fuel prices has come in tandem with a growth in the transport sector's demand for energy, contributing to a rise in both fuel costs and carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect of variations in demand is studied through analyses with different demand scenarios, and useful energy demand is an important input to the LEAP model [8]. The LEAP software includes the following features: a prediction tool, tools for analyzing energy policies, tools for analyzing the physical, economic, and environmental effects of alternative energy programs, and optimization measures [7]. LEAP is an integrated modeling tool that can track energy consumption, production, and resource extraction in all sectors of an economy.…”
Section: Energy System Scenarios 2015-2050mentioning
confidence: 99%
“…There are many cases done on the direction of GHG reduction policies. For instance, Felver [7] shows Azerbaijan has committed to cutting GHG emissions by 35% by 2030 under the Paris Agreement. By applying LEAP, a well-regarded forecasting model based on inventories de ned under the IPCC (Intergovernmental Panel on Climate Change), GHG emissions projections are modeled in LEAP.…”
Section: Introductionmentioning
confidence: 99%